Effects of Oil Price Changes on Regional Real Income Per Capita in Kazakhstan: Panel Data Analysis - Baimaganbetov, Sabit; Kelesbayev, Dinmukhamed; Yermankulova, Rima; Izzatullaeva, Bibigul; Almukhambetova, Botagoz (International Journal of Energy Economics and Policy, 2019)
The study examines the effect of Brent oil prices on the regional real per capita income in Kazakhstan by a panel data analysis of sixteen states and a quarterly time series between the years of 2008-2015. The long-term relationship between the series was examined with the help of Westerlund (2007) cointegration test. In this context, a positive and significant relationship was found between long-term oil price changes and per capita regional real income growth. In addition, causal relations between variables were investigated by Dumitrescu and Hurlin (2012) using panel Granger causality test. Empirical findings from both the co-integration and the Granger causality test show that the increase in oil prices has an important positive effect on the real income of the Kazakhstan regions. Keywords: Kazakhstan, Oil Prices, Cross Sectional Dependence, Panel Cointegration JEL Classications:C23, E64, R11 DOI: https://doi.org/10.32479/ijeep.8081